Association between dietary fiber intake and risk of ovarian cancer: a meta-analysis of observational studies. Issue 10 (October 2018) - Huang, Xiumin; Wang, Xuelian; Shang, Jing; Lin, Yanzhen; Yang, Ying; Song, Youyi; Yu, Shengnan
Objective: To evaluate the associations between dietary fiber intake and ovarian cancer risk. Methods: A literature survey was conducted by searching the PubMed, Web of Science, and Wanfang Med Online databases up to March 1st, 2018. The effect of dietary fiber intake on ovarian cancer risk was evaluated by calculating relative risks with 95% confidence intervals (95%CI) using Stata 12.0 software. Results: A total of 17 articles with 149, 177 participants including 7609 ovarian cancer patients were included in this analysis. The summarized relative risk for ovarian cancer in participants with the highest compared with the lowest fiber intake was 0.760 (95%CI=0.702–0.823), with no significant between-study heterogeneity ( I 2 =12.4%). Subgroup analysis according to study design demonstrated positive associations in both cohort studies and case-control studies. Moreover, the results were consistent among populations from America, Europe, and Asia. No publication bias was found by Egger's test or funnel plots. Conclusion: This meta-analysis concluded that a high intake of dietary fiber could significantly reduce the risk of ovarian cancer compared with a low fiber intake.